2020
DOI: 10.3390/cells9010237
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Impairs Meiosis Resumption in Xenopus laevis Oocytes

Abstract: The role of hydrogen sulfide (H2S) is addressed in Xenopus laevis oocytes. Three enzymes involved in H2S metabolism, cystathionine β-synthase, cystathionine γ-lyase, and 3-mercaptopyruvate sulfurtransferase, were detected in prophase I and metaphase II-arrested oocytes and drove an acceleration of oocyte meiosis resumption when inhibited. Moreover, meiosis resumption is associated with a significant decrease in endogenous H2S. On another hand, a dose-dependent inhibition was obtained using the H2S donor, NaHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(84 reference statements)
2
2
0
Order By: Relevance
“…Additionally, H 2 S is produced by cumulus cells, which likely promotes CO expansion ( 19 , 86 ). The importance of H 2 S during oocyte maturation is further supported by the findings of Gelaude et al ( 72 ), who confirmed the effect of H 2 S on meiosis in amphibian oocytes.…”
Section: Detection Of H 2 S-producing Enzymes and ...supporting
confidence: 54%
See 3 more Smart Citations
“…Additionally, H 2 S is produced by cumulus cells, which likely promotes CO expansion ( 19 , 86 ). The importance of H 2 S during oocyte maturation is further supported by the findings of Gelaude et al ( 72 ), who confirmed the effect of H 2 S on meiosis in amphibian oocytes.…”
Section: Detection Of H 2 S-producing Enzymes and ...supporting
confidence: 54%
“…Additionally, H 2 S is produced by cumulus cells, which likely promotes CO expansion (19,86). The importance of H 2 S during oocyte maturation is further supported by the findings of Gelaude et al (72), who confirmed the effect of H 2 S on meiosis in amphibian oocytes. It has been previously described that H 2 S has anti-aging effects and promotes the longevity, health, and condition of many organ systems, including the fetal membranes, probably through the mammalian target of rapamycin (mTOR) signaling pathway and its downstream factor S6 kinase beta-1 (S6K1) (87)(88)(89).…”
Section: The Role Of H 2 S In Oocytessupporting
confidence: 52%
See 2 more Smart Citations